IMPLEMENTASI STANDAR PENDIDIK DAN TENAGA KEPENDIDIKAN PADA SMPN 2 TAYAN HULU KECAMATAN TAYAN HULU KABUPATEN SANGGAU - Parlindungan Hutapea E.01109056 (FISIP Universitas Tanjungpura, 2013)
This articleis written for researchers to read and observe the presence of some phenomenon’s of personnel educator who have appropriate national standards that are crucial and difficult to solving, because that the researchers need to provide an overview and understanding of the problems of implementation of the standard implementation of educators and education personnel in SMP 2 Tayan Hulu. This research uses the qualitative methods with descriptive analysis that is a method whitch in the form of searching and trailing the facts, information and truth of a problem also describe and a phenomenon that happened based on fact, data and the real information. The results of the research that more looking for the factor of communication, Disposition and Bureaucratic Structure which done of the District Education Office SMP 2 to Tayan Hulu as a spearheads of policy implementation. In this research, reasearcher find shortage information which given the District Education Sanggau Regency to the new educator. Besides this, presence the educators who have additional work such as taking care of the garden and their livestock make educators more choise that case prefer than to continue their study to ladder S1. The Implementation Standards Teachers and Education Personnel in SMP 2 Tayan Hulu should be able to work effectively if done again optimal socialization to new educators. Keywords: National Education Standards, Educators and Personnel Educators.